Semantic Analysis of Similes and Metaphors in Baz Luhrmann’s Romeo + Juliet (1996): Implications for Teaching Shakespeare’s Language - Ibanez, Viona Amavisca; Ferri K, C. Prima; Hantari, Winda Candra (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study explores how similes and metaphors function semantically in Baz Luhrmann’s Romeo + Juliet (1996) and how their interpretation is influenced by the film’s multimodal elements. Figurative language in Shakespeare’s original works, while rich and expressive, often poses comprehension challenges for modern students due to its historical and linguistic complexity. To address this, the research examines how cinematic techniques such as visuals, sound, and performance can support the teaching of Shakespeare’s figurative expressions in contemporary classrooms. Using a qualitative descriptive approach, the study analyzes 30 selected similes and metaphors from key scenes across all five acts of the film. Each expression is first interpreted semantically through comparison with its original textual context, and then examined in relation to the film’s visual and auditory cues. The analysis integrates metaphor theory and multimodal discourse analysis to reveal how meaning is shaped through both language and cinematic form. Findings show that Luhrmann’s adaptation not only preserves the poetic essence of Shakespeare’s figurative language but also enhances its interpretability for modern learners. Metaphors such as love as fire, smoke, or the sea become more accessible when reinforced by imagery, music, and actors’ expressions. The study concludes that film can serve as an effective pedagogical tool for teaching complex literary devices, fostering both semantic understanding and emotional engagement.